Khawarij dan Isu Radikalisme - H. Lalu Muhamad Fazlurrahman (UIN Mataram, 2021)
Radicalism is the opposite of the moderation values that islam has brought since 1400 years ago which attracts people to study and deepen it but many people argue that the value of moderation in islam is not complete and pure, as evidenced by the thoughts of radicalism among muslims which in its history began in an organized manner since the events of the tahkim or arbitration between Ali and Muawiyah with the emergence of the khawarij sect then continues untill now with the justification of the existing radical or extremist groups using their extreme thoughts in every action.